Pengaruh Ukuran Berat Benih dan Perendaman Larutan KNO3 Terhadap Daya Kecambah Kelapa Sawit (Elaeis guineensis Jacq.) Varietas Dyx P Sungai Pancur 1 (DUMPY) - Agus Lesmana; Dini Mufriah; Syahriandi Akbari (UNIVERSITAS LABUHANBATU, 2026)
Oil palm is a palm plant that produces edible oil, industrial oil and biodiesel (biofuel). Unfortunately, the productivity of oil palm plantations nationally is still low, especially smallholder plantations managed individually. The level of oil palm production is influenced by various factors, including environmental factors where it grows, the quality of the seeds used and cultivation and management techniques in its cultivation. The purpose of this study was to determine the effect of the weight size of oil palm seeds (Elaeis guineensis Jacq.) and soaking in KNO3 solution and the interaction of the combination between the weight size of seeds and soaking in KNO3 solution on the germination of oil palm plants (Elaeis guineensis Jacq.). This study was conducted in a research area located at the Oil Palm Research Center (PPKS) Sei Aek Pancur Tanjung Morawa Deli Serdang Regency. This research was conducted from April to June 2025. This research was conducted using a Factorial Completely Randomized Design (CRD) consisting of 2 treatment factors, namely the seed weight size factor consisting of 3 levels, namely V1: seed weight size 0≤1 gram, V2: seed weight size 1.1≤2 grams, V3: seed weight size 2.1≤3 grams. The KNO3 Soaking Factor consists of 3 treatment levels, namely P0 = Control (soaking using water for 24 hours), P1 = KNO3 concentration 0.2% + soaking time 12 hours, P2 = KNO3 concentration 0.2% + soaking time 18 hours. The parameters observed in this study were germination rate (%), germination rate index, and dormancy index (%). The effect of soaking in KNO3 solution on the germination of oil palm (Elaeis guineensis Jacq.) plants. The best treatment of several parameters in breaking oil palm seed dormancy was by soaking the seeds in KNO3 concentration of 0.6% for 18 hours. The combined interaction between seed weight size and KNO3 solution soaking on the germination of oil palm (Elaeis guineensis Jacq.) plants had a significant effect.Keywords: Oil Palm, Germination Rate, Variety